Phorbol 12,13-Dibutyrate-Induced, Protein Kinase C-Mediated Contraction of Rabbit Bladder Smooth Muscle - Wang, Tanchun; Kendig, Derek M.; Trappanese, Danielle M.; Smolock, Elaine M.; Moreland, Robert S. (Frontiers in Pharmacology, 2012)
Contraction of bladder smooth muscle is predominantly initiated by M3 muscarinic receptor-mediated activation of the Gq/11-phospholipase C β-protein kinase C (PKC) and the G12/13-RhoGEF-Rho kinase (ROCK) pathways. However, these pathways and their downstream effectors are not well understood in bladder smooth muscle. We used phorbol 12, 13-dibutyrate (PDBu) and 1, 2-dioctanoyl-sn-glycerol (DOG), activators of PKC, in this investigation. We were interested in dissecting the role(s) of PKC and to clarify the signaling pathways in bladder smooth muscle contraction, especially the potential cross-talk with ROCK and their downstream effectors in regulating myosin light chain (MLC) phosphatase activity and force. To achieve this goal, the study was performed in the presence or absence of the PKC inhibitor bisindolylmaleimide-1 (Bis) or the ROCK inhibitor H-1152. Phosphorylation levels of Thr38-CPI-17 and Thr696/Thr850 myosin phosphatase target subunit (MYPT1) were measured during PDBu or DOG stimulation using site specific antibodies. PDBu-induced contraction in bladder smooth muscle involved both activation of PKC and PKC-dependent activation of ROCK. CPI-17 as a major downstream effector, is phosphorylated by PKC and ROCK during PDBu and DOG stimulation. Our results suggest that Thr696and Thr850-MYPT1 phosphorylation are not involved in the regulation of a PDBu-induced contraction. The results also demonstrate that bladder smooth muscle contains a constitutively active isoform of ROCK that may play an important role in the regulation of bladder smooth muscle basal tone. Together with the results from our previous study, we developed a working model to describe the complex signaling pathways that regulate contraction of bladder smooth muscle.